1970
DOI: 10.1098/rspa.1970.0183
|View full text |Cite
|
Sign up to set email alerts
|

On the size, charge and number-rate of formation of carbon particles in flames subjected to electric fields

Abstract: Previous studies have shown that carbon particles in flames, being all charged, can be manipulated by electric fields so as to control their residence time and hence size, as well as their rate of formation and all the parameters of deposition on the electrodes―mass, position and form of aggregate. To gain further insight into the fundamental processes, particularly those occurring during the very early (nucleation) stages, measurements of particle mobility and detailed size analyses are now added to those of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1971
1971
2005
2005

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…42 Palmer, H. B. and Cullis, C. F., "The Formation of Carbon from Gases," Chemistry and Physics of Carbon, Vol. 5, edited by P. L. Walker 49 Wright, F. J., "The Formation of Carbon Under Well -Stirred Conditions," 12th Symposium (International) on Combustion, The Combustion Institute, Pittsburgh, Pa., 1968, pp. 867-875.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Palmer, H. B. and Cullis, C. F., "The Formation of Carbon from Gases," Chemistry and Physics of Carbon, Vol. 5, edited by P. L. Walker 49 Wright, F. J., "The Formation of Carbon Under Well -Stirred Conditions," 12th Symposium (International) on Combustion, The Combustion Institute, Pittsburgh, Pa., 1968, pp. 867-875.…”
Section: Discussionmentioning
confidence: 99%
“…This formula is supported by recent results obtained from laminar diffusion flames in which the conversion of fuel-N to N 2 depends directly on the time spent in, and temperature of, the rich flame zone. 49 Furthermore, under hot, rich conditions, the hydrocarbon-NO reaction will serve to "recycle 11 NO, thus further increasing the eventual yield of N2.…”
Section: Ljq N _____>nh (Reaction Scheme Ii)mentioning
confidence: 99%
“…With increasing field strength, concentration of ions and electrons would be reduced by their removal at the electrodes, so that charge acquisition would be slower and the field therefore less efficient in shifting the particles. It is interesting that in a recent study of carbon formation in flames it was concluded that most of the carbon particles were initially neutral and acquired charge by collision with ions; it was also concluded that the particles each carried only a single electronic charge (16).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of an electric field on soot formation in laminar hydrocarbon flames has been investigated experimentally and theoretically for a long time (see, for example, [1][2][3][4][5][6]). The characteristics of the action of an electric field on the flame geometry [1][2][3][4] and nitrogen oxide emission [5] have been studied.…”
mentioning
confidence: 99%
“…The characteristics of the action of an electric field on the flame geometry [1][2][3][4] and nitrogen oxide emission [5] have been studied. In [5] it was reported on the possibility of using a constant electric field for extracting soot from a laminar propane flame.…”
mentioning
confidence: 99%